Penerapan Ejaan Bahasa Indonesia Yang Disempurnakan Dalam Penulisan Karya Ilmiah Mahasiswa Di Perguruan Tinggi - Gusnayetti, Gusnayetti; Handrina, Emi (CV. ITTC INDONESIA, 2024)
In writing scientific papers, apart from vocabulary and grammar, spelling also plays an important role so that the writing is well organized. Indonesian spelling problems in writing scientific papers include the use of letters, the use of capital letters and italics, writing words, writing absorption elements. Examined using the General Guidelines for Improved Indonesian Spelling (1994) published by the Ministry of Education and Culture. The purpose of this writing is as follows: (1) to know the main aspects of Indonesian spelling. (2) determine students' ability to apply Indonesian spelling guidelines in writing scientific essays. The results of this research are firstly the main aspects of Indonesian spelling including the use of letters, writing words, the use of punctuation marks, and writing absorption elements. Secondly, students' ability to write scientific essays according to Indonesian spelling can be said to be quite good.